2011
DOI: 10.1590/s0034-89102011005000015
|View full text |Cite
|
Sign up to set email alerts
|

Judicialização do acesso a medicamentos no Estado de Minas Gerais, Brasil

Abstract: The phenomenon of judicialization of health in Brazil can point out failures in the public health system as some medicines demanded are included in its lists. However, it is a barrier for rational drug use and application of the National Drug Policy guidelines, especially when there are demanded medicines with no evidence of efficacy and that are not included in Brazilian Health System standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
64
2
104

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(180 citation statements)
references
References 11 publications
10
64
2
104
Order By: Relevance
“…The first year of the publications included in the review was 2005, and there was a peak in the years 2010 and 2011. The data refer to studies done in the states of Pernambuco 5 , Rio Grande do Sul 2,6 , Minas Gerais 7,8 , Rio de Janeiro 9,10,11,12 , and São Paulo 13,14,15,16,17 , besides one article that collected data directly from the Ministry of Health in Brasilia 18 . The studies that examined the most lawsuits (between 2,000 and 2,927 cases) were done in the states of São Paulo, Rio de Janeiro, and Santa Catarina 7,12,14,16,19 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first year of the publications included in the review was 2005, and there was a peak in the years 2010 and 2011. The data refer to studies done in the states of Pernambuco 5 , Rio Grande do Sul 2,6 , Minas Gerais 7,8 , Rio de Janeiro 9,10,11,12 , and São Paulo 13,14,15,16,17 , besides one article that collected data directly from the Ministry of Health in Brasilia 18 . The studies that examined the most lawsuits (between 2,000 and 2,927 cases) were done in the states of São Paulo, Rio de Janeiro, and Santa Catarina 7,12,14,16,19 .…”
Section: Resultsmentioning
confidence: 99%
“…Six studies 2,9,10,11,14,17 reported a predominance of public legal representation (Office of the Public Defender, Office of the Public Prosecutor, Offices of Municipal, State, and Federal Attorneys). In five studies 6,7,8,16,20 , most plaintiffs were represented by private attorneys. In one study, free legal aid was provided to all the plaintiffs 6 .…”
Section: Resultsmentioning
confidence: 99%
“…11,21 The estimated values of the annual treatments of the therapeutic classes most demanded judicially were burdensome. Comparison between these values and the gross domestic product (GDP) per capita of Brazil (almost R$ 17,500 in 2010) d and the average monthly income of Brazilian families (R$ 2,763.47), e corroborates the arguments of the legal decisions concerning the insuffi ciency of purchasing power among the population for buying these medications.…”
Section: Discussionmentioning
confidence: 99%
“…7 The number of lawsuits against local governments can reach close to seven thousand per year in Brazil, representing annual expenditures of up to R$ 60.4 million ($ 60.4 million). 3,4,11,21 Concession of medications is considered to be a means of judicialization of healthcare policy. 5 Researchers have suggested that judicial decisions do not take into account the possibility that there may be infl uences external to the political system capable of interfering in the incorporation of therapeutic innovations within the Brazilian National Health System (Sistema Único de Saúde, SUS), such as pressure from the pharmaceutical industry or from doctor and patient associations.…”
mentioning
confidence: 99%
“…On the other hand, requests related to medicaments belonging to other AF/ SUS programs are motivated by supply-line problems, such as insuffi cient quantity procurement or failure to meet delivery schedule. 5,7,9,10,14 Studies carried out in São Paulo and Minas Gerais in 2006 showed a high number of judicial claims requesting adalimumab and etanercept (then not yet incorporated into the SUS list) from a small group of prescribers and lawyers. Such results suggest inappropriate relationships between these professionals and the pharmaceutical companies, mischaracterizing the guarantee to the right to health as the overriding motivation in these lawsuits.…”
Section: Introductionmentioning
confidence: 99%